Prevalence of hypothyroidism in type 2 diabetic adult Indian females and its correlation with age, HbA1c, BMI and duration of diabetes - Chauhan, Devendra S.; Kushwaha, J. S.; Giri, Richa; Kushwaha , Prakhar (International Journal of Research in Medical Sciences, 2023)
Background: Patients with type 2 diabetes mellitus are more prone to thyroid disorders. Hypothyroidism in them leads to an aggravation of microvascular complications. Screening for thyroid dysfunction in diabetic patients will allow early treatment of hypothyroidism. The aim of this study was to assess the prevalence of hypothyroidism in patients with type 2 diabetes mellitus and its correlation with age, HbA1c, BMI and duration of diabetes. Methods: This was a cross sectional study that was conducted at department of medicine GSVM medical college, Kanpur. 200 female patients with type 2 diabetes mellitus attending the outpatient department without any prior history of thyroid disease, chronic liver disease or acute illness were recruited for the study. Results: Our study describes 14% prevalence of hypothyroidism (subclinical hypothyroidism 13.5%) among 200 diabetic subjects. Hypothyroidism was more common in older age group maximum seen in age group 70-79 years (66.7%). Hypothyroidism was more common in subjects having diabetes for a longer duration; maximum seen in 25-30 years group (40%). No correlation was found between BMI and hypothyroidism. Conclusions: The prevalence of hypothyroidism was 14% among female patients with type 2 diabetes mellitus in this study. Overt hypothyroidism was 0.5 % and subclinical hypothyroidism was more common (13.5%) among the study subjects. Hypothyroidism was more common in older age group. and in subjects having diabetes for longer duration. No corelation was found between prevalence of hypothyroidism and body mass index (BMI).